2010
DOI: 10.1016/j.jjcc.2009.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Waist circumference reduction is more strongly correlated with the improvement in endothelial function after acute coronary syndrome than body mass index reduction

Abstract: WC reduction is more strongly correlated with the improvement of endothelial function after ACS than BMI reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 32 publications
3
5
1
Order By: Relevance
“…First, waist circumference, and mid arm circumference or triceps skinfold were not measured as indicators of body fat. These data would have provided more definitive support for our results [18,19]. Second, the distribution of body mass index in this study was lower than that reported in studies from western countries [20,21].…”
Section: Study Limitationssupporting
confidence: 75%
“…First, waist circumference, and mid arm circumference or triceps skinfold were not measured as indicators of body fat. These data would have provided more definitive support for our results [18,19]. Second, the distribution of body mass index in this study was lower than that reported in studies from western countries [20,21].…”
Section: Study Limitationssupporting
confidence: 75%
“…The insulin dose was also decreased significantly in both the groups, and this may have resulted in the increase in body weight. The improvements in ΔHbA1c, body weight, HDL-C, and TG and the reduction in HbA1c in the empagliflozin group did not affect the FMD, although the correlation between the change in the levels of a decrease in visceral adipose tissue mass, waist circumference, and ΔFMD has been shown in previous studies [8,16]. These findings suggest that empagliflozin had no effect in improving FMD although empagliflozin is effective in improving HbA1c.…”
Section: Discussionsupporting
confidence: 51%
“…The insulin dose was also decreased signi cantly in both groups, and this might have resulted in the decrease in body weight. The improvements in ΔHbA1c, body weight, HDL-C, and TG and the reduction in HbA1c in the empagli ozin group did not affect the FMD, although the correlation among the change in the decrease in visceral adipose tissue mass, waist circumference, and ΔFMD has been shown in previous studies [8,17]. These ndings suggest that empagli ozin had no effect on improving FMD although it is effective in improving HbA1c.…”
Section: Discussionsupporting
confidence: 47%